Pain Hypersensitivity: A Bio-Psychological Explanation of Chronic Musculoskeletal Pain and Underpinning Theory - Uddin, Zakir; MacDermid, Joy C. (Scientific Research, 2014)
Hypersensitivity is a phenomenon that has a dual role: adaptive (protective) and maladaptive (pathological) based on different aspects of the pain mechanism. The mechanism of hypersensitivity has not been fully defined. However, it is known that over-excitability (too much sensitivity) of neurons can arise in both peripheral and central components of the nervous system. Pain theories can be useful in helping to explain complex phenomenon like hypersensitivity. The Gate control theory and other more bio-psychological pain models may assist us to understand a mechanism of chronic musculoskeletal pain. This article discusses a mechanism based pain model.
Keywords: Abnormal Pain; Theory; Sensitivity